2015
DOI: 10.1097/md.0000000000000808
|View full text |Cite
|
Sign up to set email alerts
|

Suggestions for Lymph Node Classification of UICC/AJCC Staging System

Abstract: This article provides suggestions for N classification of Union for International Cancer Control/American Joint Committee on Cancer (UICC/AJCC) staging system of nasopharyngeal carcinoma (NPC), purely based on magnetic resonance imaging (MRI) in intensity-modulated radiation therapy (IMRT) era.A total of 1197 nonmetastatic NPC patients treated with IMRT were enrolled, and all were scanned by MRI at nasopharynx and neck before treatment. MRI-based nodal variables including level, laterality, maximal axial diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 31 publications
(61 reference statements)
1
26
1
Order By: Relevance
“…Compared to palpation-based greatest dimension of cervical lymph nodes, the MAD measured on MRI imaging was considered to be more accurate in evaluating nodal size 22 . Although previous studies failed to demonstrate the prognostic value of nodal MAD 22 , 23 , we suggested a cervical lymph node MAD ≥ 30 mm as potential stratification factor for AJCC 2009 stage II NPC patients.…”
Section: Discussioncontrasting
confidence: 64%
“…Compared to palpation-based greatest dimension of cervical lymph nodes, the MAD measured on MRI imaging was considered to be more accurate in evaluating nodal size 22 . Although previous studies failed to demonstrate the prognostic value of nodal MAD 22 , 23 , we suggested a cervical lymph node MAD ≥ 30 mm as potential stratification factor for AJCC 2009 stage II NPC patients.…”
Section: Discussioncontrasting
confidence: 64%
“…Ma, Pan and Tham et al 24 - 26 demonstrated that RLN metastasis affects the DMFS rates of patients with NPC. The study of Tang 27 showed that no significant difference was observed between patients with and without RLN metastasis. In our study, the frequency of retropharyngeal lymph node metastasis was 56.1%.…”
Section: Discussionmentioning
confidence: 93%
“…Further analysis revealed that those with elective irradiation of level IB had a higher percentage of nodal necrosis and extracapsular spread, as well as greater maximal diameter of cervical nodes (data not shown, 43.06+/− 16.76 vs. 38.58 +/− 17.07 mm, p = 0.049). Nodal necrosis [ 27 ] and maximal diameter [ 28 , 29 ] were proven to be prognostic factor for regional relapse, thus partially explaining the intriguing results. In addition, level IB was electively included in the CTV by the attending physician’s decision, based on clinical and imaging characteristics.…”
Section: Discussionmentioning
confidence: 99%